1987
DOI: 10.1002/cne.902610206
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin cells in the medial amygdala of the rat project to the lateral septum and ventral hippocampus

Abstract: The rat brain contains a large number of vasopressin (VP) immunoreactive fibers, the sites of origin of which have not yet been established completely. For instance, the sources of VP fiber systems in the amygdala, ventral hippocampus (VH), mediodorsal thalamic nucleus, ventral tegmental area, and dorsal raphe yet remain obscure. These VP fibers may originate in any of the recently described extrahypothalamic VP cell groups, viz., medial amygdaloid nucleus (AME), dorsomedial hypothalamic nucleus, or locus coer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
138
1
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(152 citation statements)
references
References 40 publications
11
138
1
2
Order By: Relevance
“…Amygdalar neurons send axons to the vicinity of the mamillary nuclei directly (Hopkins and Holstege, 1978;Krettek and Price, 1978;Price and Amaral, 1981;Caffé et al, 1987;Canteras et al, 1992) and via a synapse in the bed nucleus of the stria terminalis (Price et al, 1987;Swanson, 1987). Neurons of the mamillary nuclei provide strong input to the limbic thalamus (Seki and Zyo, 1984;Hayakawa and Zyo, 1989;Shibata, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Amygdalar neurons send axons to the vicinity of the mamillary nuclei directly (Hopkins and Holstege, 1978;Krettek and Price, 1978;Price and Amaral, 1981;Caffé et al, 1987;Canteras et al, 1992) and via a synapse in the bed nucleus of the stria terminalis (Price et al, 1987;Swanson, 1987). Neurons of the mamillary nuclei provide strong input to the limbic thalamus (Seki and Zyo, 1984;Hayakawa and Zyo, 1989;Shibata, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Also, while key anatomical sites have been identified, their interactions with one other, as well as the interactions of Avp with other neurotransmitter systems are still poorly understood. The vasopressinergic projections from the BNST and MeA to the caudal LS are important for aggression and are androgen-dependent (De Vries et al, 1984;De Vries et al, 1985;van Leeuwen et al, 1985;Caffe et al, 1987;Compaan et al, 1993;De Vries and Miller, 1998). The anterior hypothalamus (AH) is also consistently implicated in the regulation of aggression and Avpr1a in this area demonstrates considerable plasticity, which is discussed in section 2.1.1.2 (Ferris et al, 1989;Albers et al, 2006;Askew et al, 2006).…”
Section: Social Behaviormentioning
confidence: 99%
“…While V2 receptors are responsible for the effects of VP on water homeostasis in the kidney, V1 receptors mediate the effects of VP in other tissues, including the brain (5,6). VP produced in the medial amygdala and the bed nucleus of the stria terminalis projects to the lateral septum and ventral hippocampal sites where VP acting through V1 VP receptors affects memory and behavior (7,8). Previous studies showed that VP has trophic actions in a variety of cells and primary tissues including neurons (9).…”
Section: Introductionmentioning
confidence: 99%